Characteristics and Genomic Diversity of Measles Virus From Measles Cases With Known Vaccination Status in Shanghai, China - Cui, Xiaoxian; Li, Yunyi; Yang, Yuying; Tang, Wei; Li, Zhi; Chen, Hongyou; Li, Yang; Cui, Xinyi; Huang, Zhuoying; Sun, Xiaodong; Xu, Songtao; Zhang, Yan; et al. (Frontiers in Medicine, 2022)
Although the highly effective measles vaccine has dramatically reduced the incidence of measles, measles and outbreaks continue to occur in individuals Although the incidence of measles has been dramatically reduced by the highly effective measles vaccine, cases of measles and outbreaks continue to occur in individuals who received the measles vaccinemeasles-containing vaccine because of immunization failure. In this study, patients who have definite records about immunization were enrolled based on measles surveillance in Shanghai, China, from 2009 to 2017, and genomic characteristics regarding viruses retrieved from these cases could provide insights into immunization failure. In a number of 147 complete genomes of measles virus were obtained from the laboratory-confirmed cases through Illumina Miseq. Epidemiological and genetic characteristics of the measles virus were focused including information about age, gender, immunization record, variation and evolution of the whole genome. Furthermore, systematic genomics using phylogeny and selection pressure approaches were analyzed. Our analysis based on the whole genome of 147 isolates revealed four clusters: two for the genotype H1 (clusters named H1-A, including 73 isolates; H1-B, including 72 isolates) and the other 2 for D8 and B3, respectively. Estimated nucleotide substitution rates of genotype H1 measles virus derived using genome and individual genes are lower than other genotypes. Our study contributes to global measles epidemiology and proves that whole genome sequencing was a useful tool for more refined genomic characterization. After all, tThe conclusion indicates that vaccination may have an effect on virus evolution. However, no major impact was found on the antigenicity in Shanghai isolates.